2018
DOI: 10.1182/bloodadvances.2018016089
|View full text |Cite
|
Sign up to set email alerts
|

Partial trisomy 21 contributes to T-cell malignancies induced by JAK3-activating mutations in murine models

Abstract: JAK3-activating mutations are commonly seen in chronic or acute hematologic malignancies affecting the myeloid, megakaryocytic, lymphoid, and natural killer (NK) cell compartment. Overexpression models of mutant JAK3 or pharmacologic inhibition of its kinase activity have highlighted the role that these constitutively activated mutants play in the T-cell, NK cell, and megakaryocytic lineages, but to date, the functional impact of JAK3 mutations at an endogenous level remains unknown. Here, we report a JAK3 kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Reproducing the multi-step pathogenesis seen in patient samples by adding a third event in the Ts1Rhr/Gata1s model has provided insight on the role of trisomy 21 in TMD/ML-DS development. First, endogenous expression of JAK3 activating mutations enhance a TMD phenotype during fetal hematopoiesis alone, reinforcing the concept of developmental stage selectivity [95]. Moreover, bone marrow transplantation assays revealed that MPL W515L overexpression functionally cooperates with Gata1s and Ts1Rhr to drive megakaryocytic hyperplasia presenting with phenotypic features of DS-AMKL [63].…”
Section: Partially Trisomic Mice As Models To Study Ds-leukemiamentioning
confidence: 73%
See 1 more Smart Citation
“…Reproducing the multi-step pathogenesis seen in patient samples by adding a third event in the Ts1Rhr/Gata1s model has provided insight on the role of trisomy 21 in TMD/ML-DS development. First, endogenous expression of JAK3 activating mutations enhance a TMD phenotype during fetal hematopoiesis alone, reinforcing the concept of developmental stage selectivity [95]. Moreover, bone marrow transplantation assays revealed that MPL W515L overexpression functionally cooperates with Gata1s and Ts1Rhr to drive megakaryocytic hyperplasia presenting with phenotypic features of DS-AMKL [63].…”
Section: Partially Trisomic Mice As Models To Study Ds-leukemiamentioning
confidence: 73%
“…Trisomy 21 has been shown to be an independent risk factor in follicular lymphoma [140]. Gain of chromosome 21 is seen in 8.5% of cutaneous T-cell lymphoma (CTCL) [141,142], and its role in CTCL development has been assessed in vivo in cooperation with JAK3 activating mutations, through establishment of a trisomic murine model of CTCL [95]. However, the chromosome 21 genes involved in these disorders and the associated molecular mechanisms require further investigation.…”
Section: Gain Of Chromosome 21 In Other Hematological Malignanciesmentioning
confidence: 99%
“…However, these studies involved overexpression of the mutant JAK3 across multiple cell lineages also expressing wild-type mouse Jak3, in contrast to introducing the mutation into the endogenous protein expressed from its native promoter within its normal cellular context. Notably, a mouse Jak3 A572V knock-in model exhibited a more similar phenotype to the zebrafish model, with progressive expansion of CD8+ T cells and minor skin pathology, with a fully penetrant, lethal disease only manifest in cooperation with partial trisomy 21 [ 57 ]. These more physiologically relevant models emphasize the importance of additional co-operating mutations for leukemic transformation, as is observed in humans [ 3 , 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the four mammalian JAKs, JAK3 is unique in having restricted expression in hematopoietic cells, particularly within the lymphoid compartment [ 18 ]. JAK3 exclusively associates with the common interleukin-2 receptor gamma common (IL-2Rγc) chain that is shared by the receptors of several cytokines critical for lymphopoiesis, specifically IL-2, IL-4, IL-7, IL-9, IL-15 and IL-21 [ 57 ]. JAK1 has been shown to be critical for signaling from these receptors [ 20 , 54 ], which occurs via several intracellular signaling pathways, but particularly STAT5 [ 34 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…DS-ALL blasts harbor extensive genetic heterogeneity; along with the characteristic trisomy 21, somatic alterations leading to JAK2 activation, CRLF2 overexpression, and loss of IKZF1 and PAX5 are common (5). Given that trisomy of chromosome 21 (HSA21) causes DS, there has been ongoing investigation into the role of aberrant regulation of HSA21 genes in leukemogenesis (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%